2015
DOI: 10.1007/s11695-015-1781-9
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Near Infrared-Guided Surgery in Morbidly Obese Subjects Undergoing Laparoscopic Cholecystectomy

Abstract: Fluorescent cholangiography is a useful technique in the obese and non-obese population. Obesity does not affect fluorescence visualization of bile ducts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
1
28
1
2
Order By: Relevance
“…The RCT was not powered to visualize deep bile duct structures, but the limited visualization rate in the fluorescence cholangiography group was probably due to low penetration of the emitted fluorescent light through the overlying liver and fatty tissue. A high BMI may hinder visualization of the bile ducts, although findings have not been uniform. The inability of fluorescence cholangiography to visualize the left and right hepatic ducts was not at the expense of its ability to obtain the critical view of safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RCT was not powered to visualize deep bile duct structures, but the limited visualization rate in the fluorescence cholangiography group was probably due to low penetration of the emitted fluorescent light through the overlying liver and fatty tissue. A high BMI may hinder visualization of the bile ducts, although findings have not been uniform. The inability of fluorescence cholangiography to visualize the left and right hepatic ducts was not at the expense of its ability to obtain the critical view of safety.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous investigations were small, prospective non‐controlled and controlled studies, and these indicated that the ability of fluorescence cholangiography to visualize the critical junction was equal to that of X‐ray cholangiography. A recent RCT including 639 patients compared fluorescence cholangiography with white light (normal vision) and not with X‐ray cholangiography as the standard.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with current literature, we did not find significant differences in BMI in our patients in relation to successful or unsuccessful imaging of bile duct structures. 44 We hypothesize that other patient and surgical-related factors, including inflamed tissue, may interfere with and influence the success rate of fluorescence visualization of the bile ducts in complicated cases.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies were stratified to the 0.05 mg/kg bodyweight group encompassing 274 patients [2830, 32, 34, 40]. One study reported on visualization of the CD-j before dissection with positive identification in 35 of 35 cases [34].…”
Section: Resultsmentioning
confidence: 99%